Room-light-induced indoor air purification using an efficient Pt/N-TiO2 photocatalyst - Sun, Hongqi; Ullah, Ruh; Chong, Siewhui; Ang, Ha Ming; Tade, Moses; Wang, Shaobin (elsevier, 2011)
A conceptual air purifier harvesting fluorescent room lights was tested in this study. Visible photocatalysis was applied to facilitate the degradation of volatile organic compounds (VOCs) on a highly efficient visible light photocatalyst, Pt/N-TiO2 synthesised via a sol–gel process. The as-prepared photocatalyst was characterised by many techniques, such as XRD, XPS, UV–vis DRS, N2 adsorption and SEM, etc. XPS spectra revealed that platinum was at a chemical state of 2+, while nitrogen existed as NOx species. The unique chemical compositions made the photocatalyst respond to visible light with a band gap of 2.69 eV, and present a broad absorption shoulder extended further into infrared region. The photocatalytic activities under irradiations of λ > 387, 430 and 490 nm were evaluated by photodegradation of phenol solutions. Under UV–vis light, the Pt/N-TiO2 exhibited 5.5 times higher activity than Degussa P25. Various gaseous pollutants were degraded by employing the Pt/N-TiO2 in a batch reactor. The capability of photodegradation of VOCs under room lights was also proven by the decomposition of gaseous toluene in a continuous reactor using fluorescent lamps (6 × 10 W). The mechanism of the enhanced activity in degradation of VOCs and potential application were discussed.